A Least Cost Analysis: Correlative Modeling of the Chaco Regional Road System. Issue 1 (20th September 2019) - Field, Sean; Heitman, Carrie; Richards-Rissetto, Heather
During the ninth through twelfth centuries A.D., Ancestral Pueblo people constructed long, straight roads that interconnected the Chaco regional system across the San Juan Basin of northwestern New Mexico. The intent and use of these features has eluded archaeological consensus, although recent research has reiterated the occurrence of long distance timber importation to Chaco Canyon. To enhance our interpretation of these features we offer a large-scale least cost analysis wherein optimal pathways that are modeled to simulate timber importation are compared to the actual road locations. A series of least cost paths were produced through different energy allocation algorithms, at different spatial scales, and with various origin and destination inputs. Our results reveal a strong correlation between actual road locations and modeled pathways. Therefore, we suggest that certain Chaco roads may have been specifically designed to facilitate the importation of timbers and that roads, once constructed, were the optimal pathway for the import of these resources.